The Impact of Leadership, Character, and Sanctity of the Congregational Pastor on the Spiritual Growth of the Church Members - Setya Hari Purnomo; Frederich Oscar L Lontoh; Jonathan Octavianus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
This study presents the influence of leadership, character, and sanctity of the congregational pastor on the spiritual growth of church members, specifically those attending the Alfa Omega Ketintang Baru Church in Surabaya. The aim of this research is to analyze the relationship between leadership, character, and sanctity of the congregational pastor and the spiritual growth of church members, particularly those attending the Alfa Omega Ketintang Baru Church in Surabaya. The study employs a survey method to collect data on the influence of leadership, character, and sanctity of the congregational pastor on the spiritual growth of church members. The research sample consists of 150 church members of GPdI Alfa Omega Ketintang Baru in Surabaya. Data is gathered through questionnaires and analyzed using linear regression analysis. The results of the analysis indicate a positive correlation between leadership, character, and sanctity of the congregational pastor and the spiritual growth of church members. The research finds that improvements in leadership, character, and sanctity of the congregational pastor are associated with an increase in the spiritual growth of GPdI Alfa Omega Ketintang Baru church members in Surabaya. The results are as follows: When looking at the population, a t-value of 4.321 for leadership, 3.378 for character, and 5.721 for sanctity is obtained, which is significant at a < 0.05 level. This implies that the variables of leadership, character, and sanctity of the congregational pastor significantly influence the spiritual growth of GPdI Alfa Omega Ketintang Baru church members in Surabaya. Future studies could expand the scope of this research by involving more variables that affect the spiritual growth of church members. Additionally, it is essential to conduct evaluations of church programs, collaborate with mission agencies, and implement effective management systems to enhance the spiritual quality of Christians, the analysis also yielded an R-squared value (Coefficient of Determination) of 0.790 or 79.0%. This means that the contribution of the variables Leadership, Character, and Sanctity of the Congregation's Leader in shaping the Spiritual Growth of the GPdI Alfa Omega Congregation in Ketintang Baru, Surabaya, is 79.0%, while the remaining 21% is influenced by other factors outside the research model.